Curing Temperature Effects on the Tensile Properties and Hardness of γ−Fe2O3 Reinforced PDMS Nanocomposites. (16th July 2020) - Konku-Asase, Yvonne; Yaya, Abu; Kan-Dapaah, Kwabena
Abstract : The mechanical properties of plain polydimethylsiloxane (PDMS) and its nanocomposites have been exploited for various theranostic biomedical applications. Although several research groups have investigated the effects of preparation conditions—especially curing temperature and time—on bulk mechanical properties of plain PDMS, there are no reported similar studies for its nanocomposites. In this study, mechanical properties of PDMS reinforced by different volume fractions (ϕ mnp = 0 – 2 vol. %) of γ -Fe 2 O 3 nanoparticles (NPs) were investigated and quantitative data presented for different curing temperatures (25, 100, and 150°C). To a large extent, γ -Fe 2 O 3 NPs were uniformly dispersed in the PDMS matrix with no primary chemical bonds formed. For the temperatures tested, the data showed an increase for Young's modulus (E ) of about 170% (1.36–3.71 MPa) and a decrease of the ultimate tensile strength (UTS ) of about 65% (6.48 – 2.93 MPa) with increasing concentration of the NPs. Furthermore, hardness (Shore A) (H ) increased with curing temperature but decreased with concentration. Based on the findings, we conclude that the linear relationship between the calculated mechanical properties (E, UTS, H ) and small ϕ mnp is independent of the curing temperature. The experimental data provide useful background information for the selection of processing parameters for PDMS nanocomposite fabrication.